Enhancing tool life of silicon nitride inserts via hybrid microwave post sintering - Mohamed Ariff, Tasnim Firdaus; Ibrahim, Husna Izzati; Roselley, Noor Sheila; Iqbal, Mohammad; Hilmy, Irfan; -, Suryanto (IENSI, 2014)
Silicon nitride is in the group of hard covalent materials (Homlberg and Matthews, 1994) and often has amorphous structures with the atomic bonding which are formed with very high cohesive forces (Grzesik, 2008) that can withstand high temperatures, higher resistance to abrasive wear and improved oxidation and chemical resistance (Kalpakjian, 2013). Tool wear is undeniably a problem that will occur regardless how fascinating and magnificent the tool properties are. Tool wear is an important parameter that must be controlled so that the tool life will be prolonged. The properties in Silicon Nitride (Si3N4) are knowingly outstanding. However, the wear will be influenced with the type of work material, machining parameters and processing time. So if tool wear is high, replacement of tools will become faster and eventually result in increasing machining cost. A new technique using post sintering via hybrid microwave energy is developed for minimizing tool wear as well as increasing tool life. In microwave sintering, it involves energy conversion which is different from the conventional sintering that involves energy transfer. In microwave sintering, the heat is generated internally within the material instead of originating from external sources like in conventional heating. In the process of microwave heating, the materials absorb microwave energy themselves and then transform it into heat within the sample volume (Sorescu et al., 2007). The energy is directly transferred to the material through the interaction of electromagnetic waves with molecules leading to heating (Ebadzadeh and Valefi, 2007). Higher heating rates from hybrid microwave energy result in a more uniform heating; i.e volumetric heating, which reduces the total processing time and overall energy consumption (Ariff and Gabbitas, 2008). According to Feng and Hattori (2000), aluminium and its alloys are considered to be the most critical materials with regards to dry machining; since it possesses a high thermal conductivity, the workpiece absorbs considerable amount of heat from the machining process and may cause deformation due to its higher thermal expansion capabilities. Aluminium alloys also may cause problem related to chip formation due to its high ductility. T6061 Aluminum alloy has a wide range of mechanical and corrosion resistance properties as well as having most of the good qualities of aluminum. It is used in many applications from aircraft structures, yacht construction, truck bodies, bicycle frames to screw machine parts. However, Ariff et al. (2013) have successfully dry machined T6061 aluminium alloy using Si3N4 with insignificant rise in temperature compared to traditional wet machining. Nevertheless, the tool life cannot be maintained even though there is only a slight decrease (1-10%) when compared to wet machining.